1991
DOI: 10.1093/eurheartj/12.suppl_d.171
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial catecholamine concentrations in dilated cardiomyopathy and heart failure of different origins

Abstract: Myocardial catecholamine concentrations were determined in endomyocardial biopsies from patients with heart failure to assess if tissue catecholamine levels relate to the severity of myocardial damage or the aetiology of the underlying disease. Methodological studies revealed a good reproducibility of catecholamine determinations in biopsies; the variance between paired biopsies was below 17% when myocardial catecholamines were related to non-collagen protein (NCP). Myocardial norepinephrine (in pg micrograms-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
0
14
0
2
Order By: Relevance
“…In the past, many clinical trials evaluated the pronounced antihypertensive and cardioprotective effects of ACE inhibitors, and in this context, the contributions of diminished plasma noradrenaline levels to their antihypertensive and cardioprotective effects were discussed. The therapeutic significance of this action was revealed for the treatment of heart failure where a pathological sympathetic stimulation was associated with decreased cardiac noradrenaline levels (Regitz et al, 1991) due to an impairment of neuronal catecholamine uptake (Böhm et al, 1995). Kawai et al (1999) were the first to demonstrate that cardiac noradrenaline content in heart failure is increased by ACE inhibitors due to an enhanced cardiac neuronal uptake of noradrenaline; this should reflect one of the cardioprotective mechanisms of ACE inhibitors.…”
mentioning
confidence: 99%
“…In the past, many clinical trials evaluated the pronounced antihypertensive and cardioprotective effects of ACE inhibitors, and in this context, the contributions of diminished plasma noradrenaline levels to their antihypertensive and cardioprotective effects were discussed. The therapeutic significance of this action was revealed for the treatment of heart failure where a pathological sympathetic stimulation was associated with decreased cardiac noradrenaline levels (Regitz et al, 1991) due to an impairment of neuronal catecholamine uptake (Böhm et al, 1995). Kawai et al (1999) were the first to demonstrate that cardiac noradrenaline content in heart failure is increased by ACE inhibitors due to an enhanced cardiac neuronal uptake of noradrenaline; this should reflect one of the cardioprotective mechanisms of ACE inhibitors.…”
mentioning
confidence: 99%
“…It is very difficult to study a control group consisting of healthy individuals for comparison with diseased groups due to ethical problems. However, the literature has shown some control groups consisting of volunteer prisoners and patients previously suspected of having myocarditis, hemochromatosis, and endomyocardial fibrosis who underwent endomyocardial biopsy, but whose biopsies were diagnosed as normal 6,12,14,19 . In these cases, the levels of myocardial norepinephrine were similar to those found in patients with coronary artery disease with normal left ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other studies showed the relation between left ventricular ejection fraction (LVEF) and the intramyocardial norepinephrine concentration in dilated valvular, ischemic and hypertrophic cardiomyopathy [12][13][14][15] . Chronic Chagas' cardiomyopathy is characterized by an intense reduction in the heart neuronal population, as documented in necroscopic studies of chagasic patients who died of heart failure 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Šių pokyčių dydis priklauso nuo vainikinių kraujagyslių stenozės laipsnio, miokardo infarkto apimties ir stadijos (22,23). Tiriant dešiniosios ausytės miokardo nervinį rezginį, šio rezginio pokyčių priklausomumo nuo vainikinių kraujagyslių stenozės laipsnio įrodyti nepavyko.…”
Section: Rezultatų Aptarimasunclassified